Using Partial Reconfiguration and Message Passing to Enable FPGA-Based Generic Computing Platforms. (31st October 2011) - Saldaña, Manuel; Patel, Arun; Liu, Hao Jun; Chow, Paul
Abstract : Partial reconfiguration (PR) is an FPGA feature that allows the modification of certain parts of an FPGA while the rest of the system continues to operate without disruption. This distinctive characteristic of FPGAs has many potential benefits but also challenges. The lack of good CAD tools and the deep hardware knowledge requirement result in a hard-to-use feature. In this paper, the new partition-based Xilinx PR flow is used to incorporate PR within our MPI-based message-passing framework to allow hardware designers to create template bitstreams, which are predesigned, prerouted, generic bitstreams that can be reused for multiple applications. As an example of the generality of this approach, four different applications that use the same template bitstream are run consecutively, with a PR operation performed at the beginning of each application to instantiate the desired application engine. We demonstrate a simplified, reusable, high-level, and portable PR interface for X86-FPGA hybrid machines. PR issues such as local resets of reconfigurable modules and context saving and restoring are addressed in this paper followed by some examples and preliminary PR overhead measurements.